Molecular and microscopic characterization of a novel Eastern grey kangaroopox virus genome directly from a clinical sample. Issue 1 (December 2017) - Sarker, Subir; Roberts, Hayley; Tidd, Naomie; Ault, Shayne; Ladmore, Georgia; Peters, Andrew; Forwood, Jade; Helbig, Karla; Raidal, Shane
Abstract Poxviruses are large DNA viruses with varying zoonotic potential, and are recognised in a broad range of wildlife. Although poxviruses have been detected in kangaroos, their genetic relationships to poxviruses in other animals and humans is not well understood. Here, we present a novel genome sequence of a marsupial poxvirus, theEastern grey kangaroopox virus (EKPV-NSW), isolated from a wild eastern grey kangaroo. In the present study, histopathologically confirmed epidermal pox lesions were used to recover the full-length viral genome and perform electron microscopic analysis, with both immature virions and intracellular mature virions detected. Subsequent analysis of the EKPV-NSW genome demonstrated the highest degree of sequence similarity with EKPV-SC strain (91.51%), followed by WKPV-WA (87.93%), and MOCV1 (44.05%). The novel EKPV-NSW complete genome encompasses most of the chordopoxviruses protein coding genes (138) that are required for genome replication and expression, with only three essential protein coding genes being absent. The novel EKPV-NSW is missing 28 predicted genes compared to the recently isolated EKPV-SC, and carries 21 additional unique genes, encoding unknown proteins. Phylogenetic and recombination analyses showed EKPV-NSW to be the distinct available candidate genome of chordopoxviruses.